A method for removing impurities from quartz inclusions by hydrothermal stripping combined with acid leaching

Through the combined hydrothermal erosion and acid leaching method, the gas-liquid inclusion impurities in quartz sand are removed by hydrothermal reaction and acid leaching process, the problem of hydrofluoric acid pollution in the existing technology is solved, and the industrial production of high-purity quartz sand is realized , with the characteristics of simplicity, low energy consumption and pollution-free.

CN118978163BActive Publication Date: 2025-01-10NORTHEASTERN UNIV CHINA
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411471073.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-22
Publication Date
2025-01-10
Estimated Expiration
2044-10-22

AI Technical Summary

Technical Problem

The prior art relies on hydrofluoric acid when removing gas-liquid inclusion impurities in quartz sand, which leads to environmental pollution and is difficult to meet the industrial production needs of high-purity quartz sand.

Method used

The hydrothermal erosion combined with acid leaching method was used to destroy the gas-liquid inclusions by using the hydrothermal reaction of quartz sand and calcium oxide. Then, dilute nitric acid and sodium carbonate solutions were used to remove hard silica calcium stone, and high purity was obtained through acid leaching, cleaning and filtration. Quartz sand avoids the use of hydrofluoric acid.

Benefits of technology

It realizes deep purification of high-purity quartz sand, with simple process flow, low energy consumption and pollution-free, and is suitable for large-scale industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118978163B_ABST
    Figure CN118978163B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of high-purity quartz sand processing, and discloses a method for removing impurities in quartz inclusions by hydrothermal stripping combined with acid leaching. The gas-liquid inclusions on the surface of the quartz sand are destroyed by the hydrothermal reaction of quartz sand and calcium oxide, and then the xonotlite generated by the reaction is removed by dilute nitric acid and sodium carbonate solution; then, the impurities soluble in acid and the excess acid solution are removed by acid leaching, washing, and filtering to obtain pure quartz sand. The technology utilizes the hydrothermal method to destroy the gas-liquid inclusions, avoids the use of hydrofluoric acid in the acid leaching process, can effectively reduce the environmental pollution caused by the acid leaching process, and shows excellent potential for industrial application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of high-purity quartz sand processing, in particular to a method for removing quartz inclusion impurities by hydrothermal stripping combined with acid leaching. Background Art

[0002] High-purity quartz sand is an important strategic resource, mainly used in emerging industries such as photovoltaics, semiconductors, aviation, and military industry. High-end industries have very high requirements for the purity of quartz sand, among which the purity requirement for quartz sand used to produce quartz crucibles needs to be higher than 99.995%.

[0003] The preparation of high-purity quartz sand has strict requirements on the quartz sand ore. my country currently lacks high-quality ore resources that can be used to prepare 4N5 grade and above high-purity quartz. Therefore, deep purification of vein quartz and other ores is particularly important for the development of my country's high-purity quartz industry. However, some impurities in quartz sand exist in the form of gas-liquid inclusions. These impurities are difficult to remove through conventional flotation acid leaching processes and are the main factors affecting the purity of quartz. Therefore, destroying the gas-liquid inclusions by physical or chemical means to remove the impurities in them is the key to deep purification of quartz.

[0004] CN118047389A destroys gas-liquid inclusions by calcination and water quenching, and then uses mixed acid leaching with a mass ratio of hydrochloric acid, hydrofluoric acid and sulfuric acid of 3:1:1 and a mass concentration of 10-20%.

[0005] CN117923499A uses microwave acid leaching after calcination and water quenching to remove gas-liquid inclusion impurities in quartz sand; although calcination and water quenching can use the difference in physical properties between quartz and gas-liquid inclusions to induce cracks in the inclusions through the principle of "thermal expansion and contraction", this process can only destroy a small amount of gas-liquid inclusions. During the acid leaching process, a certain amount of hydrofluoric acid needs to be added to assist in destroying the inclusions, and waste liquid containing hydrofluoric acid is prone to cause environmental pollution.

[0006] CN118047388A adopts the process of pickling-calcining, water quenching and acid leaching to purify quartz sand. The pre-pickling method is used to prevent free impurities in the quartz sand from entering the gas-liquid inclusions during the calcination process and affecting the acid leaching effect.

[0007] Although the above three processes can produce quartz sand with a purity of 4N or above, they still rely on hydrofluoric acid in the acid leaching process, which is not in line with China's industrial development policies and local industry access conditions, and greatly limits industrial applications. Summary of the invention

[0008] In order to solve the bottleneck problem existing in the above-mentioned prior art, and in view of the technical defects existing in the removal of gas-liquid inclusion impurities in quartz sand, the present invention aims to provide a method for removing impurities in quartz inclusions by hydrothermal stripping combined with acid leaching, and selects non-polluting calcium oxide to destroy gas-liquid inclusions, which is conducive to the industrial production of high-purity quartz sand. The method has the characteristics of simple process flow, low energy consumption, and no pollution, and can be suitable for large-scale industrial production.

[0009] In order to achieve the above-mentioned invention purpose, the present invention provides a method for removing impurities in quartz inclusions by hydrothermal stripping combined with acid leaching, which destroys gas-liquid inclusions based on the hydrothermal synthesis method and deeply purifies quartz sand. The gas-liquid inclusions on the surface of quartz sand are destroyed by the hydrothermal reaction of quartz sand and calcium oxide, and then the xonotlite generated by the reaction is removed by dilute nitric acid and sodium carbonate solution; then, the impurities soluble in acid and the excess acid solution are removed by acid leaching, washing and filtering to obtain pure quartz sand; the method specifically includes the following steps:

[0010] A method for deep purification of quartz sand comprises the following steps:

[0011] Step 1: Add ultrapure water to quartz sand and calcium oxide in a mass ratio of 10:1 and mix them evenly to obtain a slurry with a liquid-solid ratio of 5:1. Pour the slurry into a hydrothermal reactor for hydrothermal reaction and heat at a constant temperature.

[0012] Step 2: Take the slurry out of the hydrothermal reactor, pour it into a nitric acid solution of the same volume as the slurry in step 1, heat and stir, and then filter;

[0013] Step 3: Pour the filter residue obtained in step 2 into a sodium carbonate solution having an equal volume to the nitric acid in step 2, heat and stir, and then filter to remove the residual metasilicic acid colloid in step 2;

[0014] Step 4: Pour the filter residue obtained in step 3 into an acidic solution having an equal volume to the sodium carbonate in step 3 and stir, and filter after stirring;

[0015] Step 5: Use deionized water to ultrasonically clean the filter residue to remove acid-soluble impurities and residual acid solution, and then dry to obtain high-purity quartz sand.

[0016] Furthermore, the purity of the quartz sand in step 1 is 99.74%.

[0017] Furthermore, the heating temperature of the hydrothermal reaction in step 1 is 180-220° C., and the hydrothermal reaction time is 4-8 hours.

[0018] Furthermore, the concentration of the nitric acid solution in step 2 is 4%, and the stirring speed is 200r / min.

[0019] Furthermore, the concentration of the sodium carbonate solution in step 3 is 2%, and the stirring speed is 500r / min.

[0020] Furthermore, the acidic solution in step 4 is 10% HNO 3 , 10% HCl, 10% oxalic acid mixed acid, stirring speed is 500r / min.

[0021] Furthermore, the ultrasonic frequency in step 5 is 40 kHz, and the high-temperature drying temperature is 100-140°C.

[0022] Compared with the prior art, the present invention has the following beneficial effects: the present invention uses quartz concentrate after flotation as raw material, adopts low-temperature hydrothermal method to destroy gas-liquid inclusions on the surface of quartz sand, and adopts mixed acid leaching process to remove gas-liquid inclusion impurities and some intercrystalline impurity elements in quartz sand. The technology uses hydrothermal method to destroy gas-liquid inclusions, avoids the use of hydrofluoric acid in the acid leaching process, can effectively reduce environmental pollution caused by the acid leaching process, and shows excellent industrial application potential. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 The present invention is a process flow chart of a method for removing impurities in quartz inclusions by hydrothermal stripping combined with acid leaching. DETAILED DESCRIPTION

[0024] The present invention is further described below in conjunction with specific examples, but the present invention is not limited in any way. To avoid redundant description, the raw materials in the following examples are all commercially available products unless otherwise specified, and the methods used are all conventional methods unless otherwise specified.

[0025] The purity of quartz sand and the content of impurity elements are determined according to GB / T 32650 "Detection of trace elements in quartz sand by inductively coupled plasma mass spectrometry".

[0026] like Figure 1 As shown, a method for deep purification of flotation quartz concentrate is provided, wherein the flotation quartz sand and calcium oxide are subjected to hydrothermal reaction, and then surface silicates are removed by using nitric acid and sodium carbonate solution, and then the quartz sand is acid-leached by using a mixed acid prepared by hydrochloric acid, nitric acid, and oxalic acid to prepare high-purity quartz sand; the method specifically comprises the following steps:

[0027] Step 1: Mix quartz sand and calcium oxide in a mass ratio of 10:1 and an appropriate amount of ultrapure water to evenly prepare a slurry with a liquid-solid ratio of 5:1, pour the slurry into a hydrothermal reactor for hydrothermal reaction, and place it in a temperature oven and heat it at a constant temperature of 180~220℃ for 4~8h.

[0028] Step 2: Take the slurry out of the reactor, pour it into a nitric acid solution of the same volume as the slurry in step 1, heat it until it is stirred, and filter it;

[0029] Step 3: Pour the filter residue into a sodium carbonate solution of equal volume to the nitric acid in step 2, heat, stir and filter to remove the residual metasilicic acid colloid in step 2.

[0030] Step 4: Pour the filter residue into an acidic solution of equal volume to the nitric acid in step 3 and stir. After stirring, filter.

[0031] Step 5: Ultrasonic cleaning of the filter residue was performed 3 times with deionized water to remove the acid-soluble impurities and the remaining acid solution, and high-purity quartz sand was obtained after drying.

[0032] The matters not described in the following embodiments are the same as the description of the above specific implementation methods.

[0033] Example 1

[0034] Step 1: Mix 20 g of quartz sand, 2 g of calcium oxide and 110 mL of ultrapure water to prepare a slurry with a liquid-to-solid ratio of 5:1, pour the slurry into a hydrothermal reactor for hydrothermal reaction, and heat it in an oven at 180°C for 6 hours.

[0035] Step 2: Take the slurry out of the hydrothermal reactor, pour it into an equal volume of nitric acid solution, heat it to 90°C, stir it for 15 minutes, and filter it;

[0036] Step 3: Pour the filter residue obtained in step 2 into an equal volume of sodium carbonate solution, heat to 100°C, stir for 10 minutes and filter to remove the residual metasilicic acid colloid in step 2;

[0037] Step 4: Pour the filter residue obtained in step 3 into an equal volume of acidic solution and stir for 6 hours, then filter after stirring;

[0038] Step 5: Ultrasonic cleaning of the filter residue was performed 3 times with deionized water to remove the acid-soluble impurities and the remaining acid solution, and high-purity quartz sand was obtained after drying.

[0039] Example 1 The contents of trace elements in quartz are shown in Table 1.

[0040] Example 2

[0041] Step 1: Mix 20 g of quartz sand, 2 g of calcium oxide and 110 mL of ultrapure water to prepare a slurry with a liquid-to-solid ratio of 5:1, pour the slurry into a hydrothermal reactor for hydrothermal reaction, and heat it in an oven at 200°C for 6 hours.

[0042] Step 2: Take the slurry out of the hydrothermal reactor, pour it into an equal volume of nitric acid solution, heat it to 90°C, stir it for 15 minutes, and filter it;

[0043] Step 3: Pour the filter residue obtained in step 2 into an equal volume of sodium carbonate solution, heat to 100°C, stir for 10 minutes and filter to remove the residual metasilicic acid colloid in step 2;

[0044] Step 4: Pour the filter residue obtained in step 3 into an equal volume of acidic solution and stir for 6 hours, then filter after stirring;

[0045] Step 5: Ultrasonic cleaning of the filter residue was performed 3 times with deionized water to remove the acid-soluble impurities and the remaining acid solution, and high-purity quartz sand was obtained after drying.

[0046] Example 2 The content of trace elements in quartz is shown in Table 1.

[0047] Example 3

[0048] Step 1: Mix 20 g of quartz sand, 2 g of calcium oxide and 110 mL of ultrapure water to prepare a slurry with a liquid-to-solid ratio of 5:1, pour the slurry into a hydrothermal reactor for hydrothermal reaction, and heat it in an oven at 220°C for 6 hours.

[0049] Step 2: Take the slurry out of the hydrothermal reactor, pour it into an equal volume of nitric acid solution, heat it to 90°C, stir it for 15 minutes, and filter it;

[0050] Step 3: Pour the filter residue obtained in step 2 into an equal volume of sodium carbonate solution, heat to 100°C, stir for 10 minutes and filter to remove the residual metasilicic acid colloid in step 2;

[0051] Step 4: Pour the filter residue obtained in step 3 into an equal volume of acidic solution and stir for 6 hours, then filter after stirring;

[0052] Step 5: Ultrasonic cleaning of the filter residue was performed 3 times with deionized water to remove the acid-soluble impurities and the remaining acid solution, and high-purity quartz sand was obtained after drying.

[0053] Example 3 The contents of trace elements in quartz are shown in Table 1.

[0054] Example 4

[0055] Step 1: Mix 20 g of quartz sand, 2 g of calcium oxide and 110 mL of ultrapure water to prepare a slurry with a liquid-to-solid ratio of 5:1, pour the slurry into a hydrothermal reactor for hydrothermal reaction, and heat it in an oven at 200°C for 4 hours.

[0056] Step 2: Take the slurry out of the hydrothermal reactor, pour it into an equal volume of nitric acid solution, heat it to 90°C, stir it for 15 minutes, and filter it;

[0057] Step 3: Pour the filter residue obtained in step 2 into an equal volume of sodium carbonate solution, heat to 100°C, stir for 10 minutes and filter to remove the residual metasilicic acid colloid in step 2;

[0058] Step 4: Pour the filter residue obtained in step 3 into an equal volume of acidic solution and stir for 6 hours, then filter after stirring;

[0059] Step 5: Ultrasonic cleaning of the filter residue was performed 3 times with deionized water to remove the acid-soluble impurities and the remaining acid solution, and high-purity quartz sand was obtained after drying.

[0060] Example 4 The contents of trace elements in quartz are shown in Table 1.

[0061] Example 5

[0062] Step 1: Mix 20 g of quartz sand, 2 g of calcium oxide and 110 mL of ultrapure water to prepare a slurry with a liquid-to-solid ratio of 5:1, pour the slurry into a hydrothermal reactor for hydrothermal reaction, and heat it in an oven at 200°C for 8 hours.

[0063] Step 2: Take the slurry out of the hydrothermal reactor, pour it into an equal volume of nitric acid solution, heat it to 90°C, stir it for 15 minutes, and filter it;

[0064] Step 3: Pour the filter residue obtained in step 2 into an equal volume of sodium carbonate solution, heat to 100°C, stir for 10 minutes and filter to remove the residual metasilicic acid colloid in step 2;

[0065] Step 4: Pour the filter residue obtained in step 3 into an equal volume of acidic solution and stir for 6 hours, then filter after stirring;

[0066] Step 5: Ultrasonic cleaning of the filter residue was performed 3 times with deionized water to remove the acid-soluble impurities and the remaining acid solution, and high-purity quartz sand was obtained after drying.

[0067] Example 5 The contents of trace elements in quartz are shown in Table 1.

[0068] Comparative Example 1

[0069] Step 1: Mix 20g of quartz sand, 2g of sodium hydroxide and 110ml of ultrapure water to prepare a slurry with a liquid-to-solid ratio of 5:1. Pour the slurry into a hydrothermal reactor for hydrothermal reaction and heat it in an oven at 200°C for 8h.

[0070] Step 2: Take the slurry out of the hydrothermal reactor, pour it into an equal volume of nitric acid solution, heat it to 90°C, stir it for 15 minutes, and filter it;

[0071] Step 3: Pour the filter residue obtained in step 2 into an equal volume of sodium carbonate solution, heat to 100°C, stir for 10 minutes and filter to remove the residual metasilicic acid colloid in step 2;

[0072] Step 4: Pour the filter residue obtained in step 3 into an equal volume of acidic solution and stir for 6 hours, then filter after stirring;

[0073] Step 5: Ultrasonic cleaning of the filter residue was performed 3 times with deionized water to remove the acid-soluble impurities and the remaining acid solution, and high-purity quartz sand was obtained after drying.

[0074] The trace element contents in the quartz of comparative example 1 are shown in Table 1.

[0075] Comparative Example 2

[0076] Step 1: 20 g of quartz sand and 100 ml of ultrapure water were mixed evenly to form a slurry with a liquid-solid ratio of 5:1. The slurry was poured into a hydrothermal reactor for hydrothermal reaction and heated in an oven at 200°C for 8 h.

[0077] Step 2: Take the slurry out of the hydrothermal reactor, pour it into an equal volume of nitric acid solution, heat it to 90°C, stir it for 15 minutes, and filter it;

[0078] Step 3: Pour the filter residue obtained in step 2 into an equal volume of sodium carbonate solution, heat to 100°C, stir for 10 minutes and filter to remove the residual metasilicic acid colloid in step 2;

[0079] Step 4: Pour the filter residue obtained in step 3 into an equal volume of acidic solution and stir for 6 hours, then filter after stirring;

[0080] Step 5: Ultrasonic cleaning of the filter residue was performed 3 times with deionized water to remove the acid-soluble impurities and the remaining acid solution, and high-purity quartz sand was obtained after drying.

[0081] The trace element contents in the quartz of Comparative Example 2 are shown in Table 1.

[0082] Table 1 Purity and metal impurity content of quartz sand in each case (unit: μg / g)

[0083]

[0084] For any technician familiar with the art, without departing from the scope of the technical solution of the present invention, the technical content disclosed above can be used to make many possible changes and modifications to the technical solution of the present invention, or modified into equivalent embodiments with equivalent changes. Therefore, any simple modification, equivalent change and modification made to the above embodiments according to the technical essence of the present invention without departing from the content of the technical solution of the present invention should still fall within the scope of protection of the technical solution of the present invention.

Claims

1. A method for removing impurities from quartz inclusions by hydrothermal stripping combined with acid leaching, characterized in that: The method comprises the following steps: Step 1: adding ultrapure water to quartz sand and calcium oxide in a mass ratio of 10:1 and mixing them evenly to obtain a slurry with a liquid-to-solid ratio of 5:1, pouring the slurry into a hydrothermal reactor and heating at a constant temperature to destroy the gas-liquid inclusions on the surface of the quartz sand; the hydrothermal reaction time is 4 to 8 hours; Step 2: Take the slurry out of the hydrothermal reactor, pour it into a nitric acid solution of the same volume as the slurry in step 1, heat and stir, and then filter; Step 3: Pour the filter residue obtained in step 2 into a sodium carbonate solution having an equal volume to the nitric acid in step 2, heat and stir, and then filter to remove the residual metasilicic acid colloid in step 2; Step 4: Pour the filter residue obtained in step 3 into an acidic solution having an equal volume to the sodium carbonate in step 3 and stir, and filter after stirring; Step 5: Ultrasonic cleaning of the filter residue with deionized water to remove acid-soluble impurities and residual acid solution, and high-purity quartz sand is obtained after drying.

2. The method according to claim 1, characterized in that The heating temperature of the hydrothermal reaction in step 1 is 180-220°C.

3. The method according to claim 1, characterized in that The purity of the quartz sand in step 1 is 99.74%.

4. The method according to claim 1, characterized in that: The concentration of the nitric acid solution in step 2 is 4%, and the stirring speed is 200r / min.

5. The method according to claim 1, characterized in that The concentration of the sodium carbonate solution in step 3 is 2%, and the stirring speed is 500r / min.

6. The method according to claim 1, characterized in that The acidic solution in step 4 is a mixed acid with a mass concentration of 10% HNO3, 10% HCl, and 10% oxalic acid, and the stirring speed is 500r / min.

7. The method according to claim 1, characterized in that The ultrasonic frequency in step 5 is 40 kHz, and the high temperature drying temperature is 120°C.

Citation Information

Patent Citations

  • Preparation method of high-purity quartz sand

    CN117923499A

  • Chemical deep purification method for high-purity quartz sand and high-purity quartz sand

    CN118047388A

  • Method for preparing high-purity quartz sand from granite pegmatite and high-purity quartz sand

    CN118047389A

  • Method for synchronously removing multiple impurities from quartz sand

    CN102424393A

  • Method of preparing highly pure silicon dioxide from silicon slag

    CN108516556A